2009
DOI: 10.1063/1.3246862
|View full text |Cite
|
Sign up to set email alerts
|

Energy transport via coordination bonds

Abstract: Vibrational energy transport in transition metal complexes involves stages where energy crosses relatively weak coordination bonds between a coordinated metal atom and the ligands. Understanding the energy transport rules on a molecular level is fundamentally important; it is also essential in relation to a recently proposed structural method, the relaxation-assisted two-dimensional infrared (RA 2DIR) technique, where the vibrational population transport time across the molecule of interest is linked to the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
62
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(65 citation statements)
references
References 54 publications
3
62
0
Order By: Relevance
“…The (ω NN , ω NN , ω CO ) pulse sequence was used in the 2DIR measurements with heterodyning at the ω CO frequencies. The delays between the three pulses, the dephasing time τ and the waiting-time T, and the delay between the third-order signal and the local oscillator, t, were controlled with interferometric precision of <0.05 fs (10). The energies of each of the IR pulses interacting with the sample were ca.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The (ω NN , ω NN , ω CO ) pulse sequence was used in the 2DIR measurements with heterodyning at the ω CO frequencies. The delays between the three pulses, the dephasing time τ and the waiting-time T, and the delay between the third-order signal and the local oscillator, t, were controlled with interferometric precision of <0.05 fs (10). The energies of each of the IR pulses interacting with the sample were ca.…”
Section: Discussionmentioning
confidence: 99%
“…The 2DIR measurements were performed using a dual-frequency three-pulse photon echo method with heterodyned detection (10,34,35). The (ω NN , ω NN , ω CO ) pulse sequence was used in the 2DIR measurements with heterodyning at the ω CO frequencies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the application of vibrational excitation to manipulate photo-induced reactions in the condensed phase is challenging due to the expected rapid intramolecular vibrational redistribution (IVR). The latter promptly (typically on the scale of a few femtoseconds to a few picoseconds) 17 scrambles memory of vibrational excitation as excited modes are typically strongly anharmonically coupled to other intramolecular modes, resulting in non-selective delocalized excitation 8,18 .However, under the right conditions, namely sufficient energetic and spatial separation from other intramolecular vibrations, certain modes can retain their vibrational excitation for significant periods of time [19][20][21] . ET can take place during or prior to vibrational relaxation of such modes, and it has been shown that the resulting rate of reaction can be greatly influenced by the vibrational state of the reactant 22-24 .…”
mentioning
confidence: 98%
“…Another important component in our system is the metal centre which acts as a vibrational energy transfer bottleneck that contributes to the localization of injected quanta of energy on either arm of the molecule. [38][39][40][41][42] Furthermore, the presence of the metal offering a two-step charge-separation process starting from a metal-to-acceptor charge transfer followed by reductive quenching from the donor is a particularly effective design strategy to achieve IR-control: 15,16,35,36 it allows the rapid population of a far-fromequilibrium gateway state where an IR pump can be introduced, and in this way perturb an otherwise symmetrical system in a spatially selective manner at a crucial crossroad where small structural and energetic fluctuations dictate the chosen electronic pathway. 43 Complementary to such excited state evolution is the ability to delay the control pulse with respect to actinic excitation, thus influencing reactivity at the decisive moments of light-induced molecular function [44][45][46][47] and circumventing the myriad of processes occurring immediately after electronic excitation, which would rapidly scramble the selectivity of mode-specific excitation.…”
Section: Control Of Et Pathways Using Targeted Vibrational Excitationmentioning
confidence: 99%